Muslim Educational Institutions in Ukraine - Alla Aristova (Українське Pелігієзнавство, 2014)
One of the essential features of the history of Islam and Muslim religious spirituality is the cult of knowledge. Islam has developed a completely different model of the relationship between faith and knowledge, knowledge of God and knowledge of the universe, religion, and science than that which was characteristic of Christianity (this is the medieval Christianity that Islam has found historically). For centuries, this difference will be startling: we will see the European civilization, where the church authorities brutally destroyed the germs of free thought and scientific thought and Muslim civilization, where the cult of knowledge acquired a sacred dimension. The widespread development of medieval Muslim culture, science and art, which has made a significant contribution to the development of world scientific thought, has been posited as the embodiment of Muslims in the life of one of the main religious duties - the acquisition of knowledge, since the path to knowledge is interpreted in Islam as a way to comprehend power and the mercy of the Almighty. "There is no better worship for Allah than gaining knowledge" - it will be written on Maktabas and madrasah. Teachers and students will quote the verses of the Qur'an: "O Lord! Increase my knowledge "! Each new Muslim ruler - from the Caliph to his advisers and ministers - had to build a mosque, his own mausoleum and ... a library.